Comparison of regional and general anesthesia in upper extremity fracture surgeries: A narrative review of evidence-based practices - Purnamasari, Yunita; Wardhana, Teddy Heri; Waloejo, Christijogo Sumartono (Edelweiss Applied Science and Technology, 2025)
Upper extremity fractures often require surgical fixation. The choice of anesthesia—general anesthesia (GA) or regional anesthesia (RA)—significantly influences perioperative outcomes. While GA remains the standard, RA, particularly peripheral nerve blocks, has gained popularity due to its potential benefits in pain management and recovery. This literature review aims to summarize current evidence comparing RA and GA for upper extremity fracture surgeries, focusing on postoperative pain control, functional recovery, length of hospital stay, patient satisfaction, and cost-effectiveness. A comprehensive search of peer-reviewed journals, clinical guidelines, and systematic reviews was conducted via PubMed, ScienceDirect, Cochrane Library, and Google Scholar for articles published between 2005 and 2024. Studies comparing RA and GA in adult patients undergoing upper extremity fracture fixation were included. Evidence suggests that RA provides superior immediate postoperative pain control and may reduce opioid consumption and hospital stay. Broader adoption requires adequate training and resource allocation. Both techniques demonstrate comparable long-term functional outcomes.